2017
DOI: 10.1007/s40071-017-0172-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary soybean meal and multienzyme on intestine histology of beluga sturgeon (Huso huso)

Abstract: This study aimed to evaluate the effect of soybean meal and multienzyme supplementation on intestinal histopathology of beluga sturgeon (Huso huso). Nine diets were formulated (40% crude protein, 13% crude fat and 4150 kcal/kg gross energy) in which fish meal was replaced by soybean meal at 0, 40 and 80% supplemented or not with 1 or 2 g/kg of multienzyme Kemin. Fish (initial weight of 820 g) were fed on experimental diets four times daily at 1% body weight for 12 weeks. From histological analyses, intact vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…Zhang et al 40 found that 75% replacement of FM with SBM resulted in significantly shorter intestinal villi and, correlated with increased enteritis and a significantly reduced growth rate in Japanese sea bass ( Lateolabrax japonicus ). Similar results were observed in beluga sturgeon ( Huso huso ), where SBM inclusion resulted in shorter and wider distal villi 41 . In addition, Wang et al 6 observed that the complete replacement of FM with SBM in diets reduced the length of the intestinal villi and also the surface area of the villi.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Zhang et al 40 found that 75% replacement of FM with SBM resulted in significantly shorter intestinal villi and, correlated with increased enteritis and a significantly reduced growth rate in Japanese sea bass ( Lateolabrax japonicus ). Similar results were observed in beluga sturgeon ( Huso huso ), where SBM inclusion resulted in shorter and wider distal villi 41 . In addition, Wang et al 6 observed that the complete replacement of FM with SBM in diets reduced the length of the intestinal villi and also the surface area of the villi.…”
Section: Discussionsupporting
confidence: 82%
“…SBM inclusion in diets has been found to trigger an inflammatory response that negatively affects the morphology of the intestines of fish. The SBM induced inflammation (enteritis) is characterized by shorter villi and a decreased capacity for absorption in the epithelial enterocytes 6 , 38 41 . Zhang et al 40 found that 75% replacement of FM with SBM resulted in significantly shorter intestinal villi and, correlated with increased enteritis and a significantly reduced growth rate in Japanese sea bass ( Lateolabrax japonicus ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dietary carob seed germ meal and soybean meal presented negative impacts on the fold height of intestinal tissue of aquatic fish (Fadel et al, 2017;Sohrabnezhad, Sudagar, & Mazandarani, 2017;Wang, Wang, Zhang, & Song, 2017). Accordingly, in order to better digest feather meal, the increasing of tryptase activity may be the compensatory response in the case of unfavourable condition of intestinal histology in this study.…”
Section: Discussionmentioning
confidence: 64%
“…Histological analysis revealed significant differences in the villus epithelium thickness of piaparas fed diets with different protein sources. The smaller thickness observed in piaparas fed soybean meal (39.3 µm) may be related to the antinutritional factors in soybeans causing the villi to taper (Van Den Ingh et al, 1991), which may trigger inflammation in the intestinal mucosa 7/9 (Sohrabnezhad et al, 2017) depending on the tolerance of each species and the type of processing (Escaffre et al, 2007).…”
Section: Discussionmentioning
confidence: 99%